Efekat apsorpcionog kolagen šava za popravku oralnog implantata na zaceljivanje rana i upalnih faktora gingivalske crevikularne tečnosti: Effect of Collagen Sutures on Oral Wound Healing - Feng, Jingjing; Yu, Qiaolong; Liu, Xiaoqing (Journal of Medical Biochemistry, 2024)
Background: To investigate the clinical value of absorbable collagen suture in the treatment of oral implant restoration. Methods: A prospective, randomized, single-blind trial was conducted in patients undergoing dental implant restoration in our hospital. The patients were divided into an absorbable group (incision closure with absorbable collagen suture) and a conventional group (incision closure with conventional suture). The incision healing time, postoperative pain degree, incision healing grade, patient satisfaction, and the levels of tumor necrosis factor-α (TNF-α), interleukin-8 (IL-8) and interleukin-6 (IL-6) in gingival crevicular fluid were compared between the two groups.Results: The absorbable group had faster incision healing times and lower postoperative pain scores on days 1 and 2, all with significant differences (P